Asymmetric impacts of climate change on thermal habitat suitability for inland lake fishes - Luoliang Xu; Zachary S. Feiner; Paul Frater; Gretchen J. A. Hansen; Robert Ladwig; Craig P. Paukert; Michael Verhoeven; Lyndsie Wszola; Olaf P. Jensen (Nature Communications)
Abstract Climate change is altering the thermal habitats of freshwater fish species. We analyze modeled daily temperature profiles from 12,688 lakes in the US to track changes in thermal habitat of 60 lake fish species from different thermal guilds during 1980-2021. We quantify changes in each species’ preferred days, defined as the number of days per year when a lake contains the species’ preferred temperature. We find that cooler-water species are losing preferred days more rapidly than warmer-water species are gaining them. This asymmetric impact cannot be attributed to differences in geographic distribution among species; instead, it is linked to the seasonal dynamics of lake temperatures and increased thermal homogenization of the water column. The potential advantages of an increase in warmer-water species may not fully compensate for the losses in cooler-water species as warming continues, emphasizing the importance of mitigating climate change to support effective freshwater fisheries management.